Morphometric evaluation of features of remodeling of chondrocites of joint surfaces of temporomandibular joint of experimental animals in hyperglycemia - Mykhailo Hnatiuk; Lesia Rubas (Kazimierz Wielki University, 2021)
Aim: to study morphometrically the peculiarities of remodeling of chondrocytes of the articular surfaces of the temporomandibular joint in hyperglycemia. Materials and methods: Quantitative morphological methods were used to study diameters of chondrocytes and their nuclei, nuclear-cytoplasmic relationship in these cells, relative volume of damaged chondrocytes, intercellular-chondrocytic relationship in mature chondrocytes of the articular surfaces of the temporomandibular joint of 45 laboratory mature white male rats with simulated diabetes. Results: A comprehensive analysis of the morphometric parameters presented in the article showed that they did not differ in the articular surfaces of the temporal fossa and mandibular head of the intact temporomandibular joint. The expressed structural changes of chondrocytes were revealed at a monthly and a two-month diabetic arthropathy of this joint. Conclusions: Proceeded studies and obtained results suggest that prolonged hyperglycemia leads to diabetic arthropathy of the TMJ, which is characterized by atrophy of chondrocytes, violation of nuclear-cytoplasmic relationships, an increase in the relative volume of damaged chondrocytes and volume of intercellular substance. The detected changes in quantitative morphological parameters depended on the duration of hyperglycemia and dominated in the cartilaginous tissue of the articular surface of the mandibular head.